Geometrielernen digital unterstützen - Räumliche Kompetenzen und individuelle Lernwege mittels adaptierbarer algorithmischer Rückmeldemöglichkeiten fördern - Bechinie, Dominik; Eilerts, Katja; Huhmann, Tobias; Lenke, Michael; Schulte, Carsten; Winkelnkemper, Felix (Beiträge zum Mathematikunterricht 2021)

Nutzung der Personas-Methode zum Umgang mit der Heterogenität von Informatik-Studierenden - Gerstenberger, Dietrich Karl-Heinz; Winkelnkemper, Felix; Schulte, Carsten (9. Fachtagung Hochschuldidaktik Informatik (HDI))

Zur neuen Bedeutung von Daten in Data Science und künstlicher Intelligenz - Höper, Lukas; Podworny, Susanne; Hüsing, Sven; Schulte, Carsten; Fleischer, Yannik; Biehler, Rolf; Frischemeier, Daniel; Malatyali, Hülya (19. GI-Fachtagung Informatik und Schule, INFOS 2021, Wuppertal, Germany, September 8-10, 2021)

Entwicklung und Rekonstruktion einer interaktionsgeprägten Sichtweise auf das komplementäre Mensch-Maschine-Verhältnis - Budde, Lea

Computers and Education – Recognising Opportunities and Managing Challenges - Passey, Don; Brinda, Torsten; Cornu, Bernard; Holvikivi, Jaana; Lewin, Cathy; Magenheim, Johannes; Morel, Raymond; Osorio, Javier; Tatnall, Arthur; Thompson, Barrie; Webb, Mary (Advancing Research in Information and Communication Technology)
Keywords: Educational technologies; Education and technologies; Digital technologies and education; Information technologies; Communication technologies; Educational technologies and research; Educational technologies and pedagogical practices; Educational technologies and policy; Educational management and technologies; Professional development and educational technologies

Data Science ab Klasse 5–Konkrete Unterrichtsvorschläge für künstliche Intelligenz unplugged und Datenbewusstsein - Podworny, Susanne; Höper, Lukas; Fleischer, Yannik; Hüsing, Sven; Schulte, Carsten (INFOS 2021–19. GI-Fachtagung Informatik und Schule)

Zur neuen Bedeutung von Daten in Data Science und künstlicher Intelligenz - Höper, Lukas; Podworny, Susanne; Hüsing, Sven; Schulte, Carsten; Fleischer, Yannik; Biehler, Rolf; Frischemeier, Daniel; Malatyali, Hülya (INFOS 2021–19. GI-Fachtagung Informatik und Schule)

Faszination 3D-Film: Entwicklung einer 3D-Konstruktion - Hüsing, Sven; Weiser, Niklas; Biehler, Rolf (mathematik lehren)

Explanation as a Social Practice: Toward a Conceptual Framework for the Social Design of AI Systems - Rohlfing, Katharina J.; Cimiano, Philipp; Scharlau, Ingrid; Matzner, Tobias; Buhl, Heike M.; Buschmeier, Hendrik; Esposito, Elena; Grimminger, Angela; Hammer, Barbara; Haeb-Umbach, Reinhold; Horwath, Ilona; Hüllermeier, Eyke; et al. (IEEE Transactions on Cognitive and Developmental Systems)
One objective of current research in explainable intelligent systems is to implement social aspects in order to increase the relevance of explanations. In this paper, we argue that a novel conceptual framework is needed to overcome shortcomings of existing AI systems with little attention to processes of interaction and learning. Drawing from research in interaction and development, we first outline the novel conceptual framework that pushes the design of AI systems toward true interactivity with an emphasis on the role of the partner and social relevance. We propose that AI systems will be able to provide a meaningful and relevant explanation only if the process of explaining is extended to active contribution of both partners that brings about dynamics that is modulated by different levels of analysis. Accordingly, our conceptual framework comprises monitoring and scaffolding as key concepts and claims that the process of explaining is not only modulated by the interaction between explainee and explainer but is embedded into a larger social context in which conventionalized and routinized behaviors are established. We discuss our conceptual framework in relation to the established objectives of transparency and autonomy that are raised for the design of explainable AI systems currently.
Keywords: Explainability; process ofexplaining andunderstanding; explainable artificial systems

Der Darstellungsflüchtigkeit im Geometrieunterricht durch digitale Unterstützung entgegenwirken - Huhmann, Tobias; Eilterts, Katja; Schulte, Carsten; Winkelnkemper, Felix (Digitales Lernen in der Grundschule II: Aktuelle Trends in Forschung und Praxis)

The Interdisciplinary Development of an Educational Game for Primary School Children--Lessons Learned - Winkelnkemper, Felix; Schulte, Carsten; Eilerts, Katja; Bechinie, Dominik; Huhmann, Tobias (EdMedia+ Innovate Learning)

Combining Ideas and Artifacts: An Interaction-Focused View on Computing Education Using a Cybersecurity Example - Terfloth, Lutz; Budde, Lea; Schulte, Carsten
In this paper, we present a novel approach to design teaching interventions for computing education, elaborated using an example of cybersecurity education. Cybersecurity education, similar to other computing education domains, often focuses on one aspect and separate themselves from the other approach. In other words, they focus on one of the two different aspects: a) either teaching how to use and to behave, or b) how technology works. Here we suggest another point of focal awareness for teaching – interaction – that allows the recombination of both approaches in a novel way, leading to a reconstruction of the teaching and learning content in a way that – as we hope – supports an understanding on a higher level and thus gives the chance to better develop agency. For this didactic reconstruction of teaching content, we use an approach called the hybrid interaction system framework. In cybersecurity training, teaching interventions oftentimes are in a way successful but seem to not lead to long-lasting changes towards secure behavior. Using simply password security as an example, we show how this new approach recombines the two different priory mentioned teaching approaches in a novel way. Within this short paper, we present our current research progress, discuss potentials and values of the approach in general, and by way of example. Our intention of this submission and early disclosure is to spark discussion and generate further insights especially regarding the following question: What implications does the hybrid interaction system approach have on learning scenarios?

Machine learning for human learners: opportunities, issues, tensions and threats - Webb, Mary E; Fluck, Andrew; Magenheim, Johannes; Malyn-Smith, Joyce; Waters, Juliet; Deschênes , Michelle; Zagami, Jason (Educational Technology Research and Development)

< Big Data> aus der Perspektive von Informatischer Bildung und Medienpädagogik - Magenheim, Johannes (MedienPädagogik: Zeitschrift für Theorie und Praxis der Medienbildung)

Data science education - Magenheim, Johannes; Schulte, Carsten (Encyclopedia of Education and Information Technologies. Cham: Springer)

Programmieren - Lehren und Lernen mit und über Medien - Schulte, Carsten; Budde, Lea; Winkelnkemper, Felix (Mobile Medien im Schulkontext)

Data Science und Big Data in der beruflichen Bildung – Konzeption und Erprobung eines Projektkurses für die Sekundarstufe II - Opel, Simone Anna; Schlichtig, Michael (Sammelband der 27. Fachtagung der BAG Berufliche Bildung)
Die Themen „Big Data“, „Künstliche Intelligenz und „Data Science“ werden seit einiger Zeit nicht nur in der breiten Öffentlichkeit kontrovers diskutiert, sondern stellen für die Ausbildung in den IT- und IT-nahen Berufen schon heute neue Herausforderungen dar, die in Zukunft durch die gesellschaftliche und technologische Weiterentwicklung hin zu einer Datengesellschaft noch größer werden. An dieser Stelle stellt sich die Frage, welche Aspekte dieses großen Themenkomplexes für Schule und Ausbildung von Wichtigkeit sind und wie diese Themen sinnstiftend und gewinnbringend in die informatische Ausbildung in verschiedenen Bildungsgängen integriert werden können. Im Rahmen des von uns im Jahr 2017 organisierten Symposiums zum Thema „Data Science“ wurden für die Bildung relevante Aspekte erörtert, wodurch als Kernelemente für den Unterricht Algorithmen der Künstlichen Intelligenz und ihre Anwendung in Industrie und Gesellschaft, Explorationen von Big Data sowie der Umgang mit eigenen Daten in sozialen Netzwerken herausgearbeitet wurden. Ziel ist, aus diesen Themenbereichen sowohl ein umfassendes Curriculum als auch Module für verschiedene Unterrichtsszenarien zu entwickeln und zu erproben. Durch diese Materialien soll es Lehrkräften aus der Informatik, Mathematik oder Technik ermöglicht werden, diese Themen auf Basis des Curriculums und der erprobten Unterrichtskonzepte selbst zu unterrichten. Hierfür wurde im Rahmen des Projekts ProDaBi (Projekt Data Science und Big Data in der Schule, https://www.prodabi.de), initiiert von der Telekom Stiftung, ein experimenteller Projektkurs entwickelt, den wir mit Schüler:innen der Sekundarstufe II an der Universität Paderborn im Schuljahr 2018/19 durchführten. Dieser Kurs enthält neben einem Modul zur Exploration von Big Data und einem weiteren Modul zum Maschinellen Lernen als Teil der Künstlichen Intelligenz auch eine Projektphase, die es in Zusammenarbeit mit lokalen Unternehmen den Schüler:innen ermöglicht, das Erlernte in ein reales Data Science-Projekt einzubringen. Aus den Erfahrungen dieses Projektkurses sowie den parallel durchgeführten Erprobungen einzelner Bausteine auch mit beruflichen Schulen werden ab dem Schuljahr 2019/20 die hierfür verwendeten Materialien weiterentwickelt und weiteren Kooperationspartnern zur Erprobung zur Verfügung gestellt. Damit wurden zum Ende des Projekts nicht nur vollständige Unterrichtsmaterialien, sondern auch ein umfassendes Curriculum entwickelt.
Keywords: Berufsbildung; vocational education; Ausbildung; training; berufliche Weiterbildung; advanced vocational education; Digitalisierung; digitalization; Unterricht; teaching; Lehrmethode; teaching method; Interdisziplinarität; interdisciplinarity; Fachdidaktik; subject didactics; Curriculum; curriculum; gewerblich-technischer Beruf; vocational/technical occupation; Fachkraft; specialist; Qualifikationsanforderungen; qualification requirements; Kompetenz; competence; Lehrerbildung; teacher training; Bundesrepublik Deutschland; Federal Republic of Germany

Understanding and Explaining Digital Artefacts - the Role of a Duality (Accepted Paper - Digital Publication Follows) - Budde, Lea; Schulte, Carsten; Buhl, Heike M.; Muehling, Andreas (Seventh International Conference on Learning and Teaching in Computing and Engineeringe)
Keywords: ⛔ No DOI found

Data science education in secondary schools: Teaching and learning decision trees with CODAP and Jupyter Notebooks as an example of integrating machine learning into statistics education - Biehler, Rolf; Fleischer, Yannik; Budde, Lea; Frischemeier, Daniel; Gerstenberger, Dietrich; Podworny, Susanne; Schulte, Carsten (New Skills in the Changing World of Statistics Education Proceedings of the Roundtable conference of the International Association for Statistical Education (IASE))

Data Science Education in Secondary School: How to Develop Statistical Reasoning When Exploring Data Using CODAP - Budde, Lea; Frischemeier, Daniel; Biehler, Rolf; Fleischer, Yannik; Gerstenberger, Dietrich; Podworny, Susanne; Schulte, Carsten (New Skills in the Changing World of Statistics Education: Proceedings of the Roundtable conference of the International Association for Statistical Education (IASE), July 2020)

Program Comprehension: Identifying Learning Trajectories for Novice Programmers - Izu, Cruz; Schulte, Carsten; Aggarwal, Ashish; I. Cutts, Quintin; Duran, Rodrigo; Gutica, Mirela; Heinemann, Birte; Kraemer, Eileen; Lonati, Violetta; Mirolo, Claudio; Weeda, Renske (Proceedings of the 2019 (ACM) Conference on Innovation and Technology in Computer Science Education, Aberdeen, Scotland, UK, July 15-17, 2019)

Einsatz von Jupyter Notebooks am Beispiel eines fiktiven Kriminalfalls - Kapp, Florian; Schulte, Carsten (Informatik für alle, 18. GI-Fachtagung Informatik und Schule, (INFOS) 2019, 16.-18. September 2019, Dortmund)

Zur Relevanz eines Prozessbereiches Interaktion und Exploration im Kontext informatischer Bildung im Primarbereich - Müller, Kathrin; Schulte, Carsten; Magenheim, Johannes (Informatik für alle, 18. GI-Fachtagung Informatik und Schule, (INFOS) 2019, 16.-18. September 2019, Dortmund)

Das RetiBNE Café - Schmidt, Ann-Katrin; Schulte, Carsten (Informatik für alle, 18. GI-Fachtagung Informatik und Schule, (INFOS) 2019, 16.-18. September 2019, Dortmund)

Critical Incidents for Technology Enhanced Learning in Vocational Education and Training - Wilke, Adrian; Magenheim, Johannes (IEEE Global Engineering Education Conference, EDUCON 2019, Dubai, United Arab Emirates, April 8-11, 2019)

Zieldimensionen für Multiplikatorinnen und Multiplikatoren früher MINT-Bildung - Köller, Olaf; Magenheim, Johannes; Molitor, Heike; Pfenning, Uwe; Ramseger, J{\; Steffensky, Mirjam; Wiesmüller, Christian; Winther, Esther; Wollring, Bernd

„Der Informatikkreis “: Kinder von drei bis zehn Jahren beim Forschen in Informatik begleiten - ein methodisch-didaktisches Material - Franke-Wiekhorst, Antonia; Günther, Christine; Brünger, Karen; Magenheim, Johannes; Romeike, Ralf (GdSU-Journal,(9))

Understanding Artificial Intelligence – A Project for the Development of Comprehensive Teaching Material - Schlichtig, Michael; Opel, Simone Anna; Budde, Lea; Schulte, Carsten (ISSEP 2019 - 12th International conference on informatics in schools: Situation, evaluation and perspectives, Local Proceedings)
Artificial intelligence (AI) has the potential for far-reaching – in our opinion – irreversible changes. They range from effects on the individual and society to new societal and social issues. The question arises as to how students can learn the basic functioning of AI systems, what areas of life and society are affected by these and – most important – how their own lives are affected by these changes. Therefore, we are developing and evaluating school materials for the German ”Science Year AI”. It can be used for students of all school types from the seventh grade upwards and will be distributed to about 2000 schools in autumn with the support of the Federal Ministry of Education and Research. The material deals with the following aspects of AI: Discussing everyday experiences with AI, how does machine learning work, historical development of AI concepts, difference between man and machine, future distribution of roles between man and machine, in which AI world do we want to live and how much AI would we like to have in our lives. Through an accompanying evaluation, high quality of the technical content and didactic preparation is achieved in order to guarantee the long-term applicability in the teaching context in the different age groups and school types. In this paper, we describe the current state of the material development, the challenges arising, and the results of tests with different classes to date. We also present first ideas for evaluating the results.
Keywords: Artificial Intelligence; Machine Learning; Teaching Material; Societal Aspects; Ethics. Social Aspects; Science Year; Simulation Game

Entwicklung und Reflexion einer Unterrichtssequenz zum Maschinellen Lernen als Aspekt von Data Science in der Sekundarstufe II - Opel, Simone Anna; Schlichtig, Michael; Schulte, Carsten; Biehler, Rolf; Frischemeier, Daniel; Podworny, Susanne; Wassong, Thomas (INFOS)

Maschinelles Lernen im Unterricht mit Jupyter Notebook - Schlichtig, Michael; Opel, Simone Anna; Schulte, Carsten; Biehler, Rolf; Frischemeier, Daniel; Podworny, Susanne; Wassong, Thomas (INFOS)

Developing Teaching Materials on Artificial Intelligence by Using a Simulation Game (Work in Progress) - Opel, Simone Anna; Schlichtig, Michael; Schulte, Carsten (WiPSCE)

Kritische Entgegnung auf die Studie "Zur Relevanz informatischer Bildung in der Schule für den Erwerb computer- bzw. informationsbezogener Kompetenzen" - Brinda, Torsten; Diethelm, Ira; Hellmig, Lutz; Magenheim, Johannes; Romeike, Ralf; Schroeder, Ulrik (MedienPädagogik: Zeitschrift für Theorie und Praxis der Medienbildung)

Evaluation of Learning Informatics in Primary Education - Views of Teachers and Students - Magenheim, Johannes; Müller, Kathrin; Schulte, Carsten; Bergner, Nadine; Haselmeier, Kathrin; Humbert, Ludger; Müller, Dorothee; Schroeder, Ulrik (Informatics in Schools. Fundamentals of Computer Science and Software Engineering - 11th International Conference on Informatics in Schools: Situation, Evolution, and Perspectives, (ISSEP) 2018, St. Petersburg, Russia, October 10-12, 2018, Proceedings)

Eye-movement Modeling Examples in Source Code Comprehension: A Classroom Study - Bednarik, Roman; Schulte, Carsten; Budde, Lea; Heinemann, Birte; Vrzakova, Hana (Proceedings of the 18th Koli Calling International Conference on Computing Education Research, Koli, Finland, November 22-25, 2018)

Are children perceiving robots as supporting or replacing humans?: first empirical results and classification of preconceptions within a theoretical framework - Müller, Kathrin; Schulte, Carsten (Proceedings of the 13th Workshop in Primary and Secondary Computing Education, WiPSCE 2018, Potsdam, Germany, October 04-06, 2018)

The computing repair cafe: a concept for repair cafes in computing edcuation - Schulte, Carsten; Krüger, Jessica; Gödecke, Andreas; Schmidt, Ann-Katrin (Proceedings of the 13th Workshop in Primary and Secondary Computing Education, WiPSCE 2018, Potsdam, Germany, October 04-06, 2018)

Proceedings of the Workshop on Eye Movements in Programming, EMIP@ETRA 2018, Warsaw, Poland, June 15, 2018

Computer Science Education: Perspectives on Teaching and learning in school - Sentance, Sue; Barendsen, Erik; Schulte, Carsten

Drafting a Data Science Curriculum for Secondary Schools - Heinemann, Birte; Opel, Simone Anna; Budde, Lea; Schulte, Carsten; Frischemeier, Daniel; Biehler, Rolf; Podworny, Susanne; Wassong, Thomas (Koli Calling)

A Framework for Computing Education: Hybrid Interaction System: The need for a bigger picture in computing education - Schulte, Carsten; Budde, Lea (Koli Calling)

The design and exploration cycle as research and development framework in computing education - Schulte, Carsten; Magenheim, Johannes; Müller, Kathrin; Budde, Lea (2017 (IEEE) Global Engineering Education Conference, (EDUCON) 2017, Athens, Greece, April 25-28, 2017)

Zieldimensionen für frühe informatische Bildung im Kindergarten und in der Grundschule - Bergner, Nadine; Köster, Hilde; Magenheim, Johannes; Müller, Kathrin; Romeike, Ralf; Schroeder, Ulrik; Schulte, Carsten (Informatische Bildung zum Verstehen und Gestalten der digitalen Welt, Proceedings der 17. GI-Fachtagung Informatik und Schule, (INFOS) 2017, 13.-15. September 2017, Oldenburg)

Ein Modell zur Analyse von Vorstellungen über Roboter und ihrer Funktionsweise - Müller, Kathrin; Schulte, Carsten (Informatische Bildung zum Verstehen und Gestalten der digitalen Welt, Proceedings der 17. GI-Fachtagung Informatik und Schule, (INFOS) 2017, 13.-15. September 2017, Oldenburg)

A theory based tool set for analysing reading processes in the context of learning programming - Budde, Lea; Heinemann, Birte; Schulte, Carsten (Proceedings of the 12th Workshop on Primary and Secondary Computing Education, WiPSCE 2017, Nijmegen, The Netherlands, November 8-10, 2017)

Zieldimensionen informatischer Bildung im Elementar-und Primarbereich - Bergner, Nadine; Köster, Hilde; Magenheim, Johannes; Müller, Kathrin; Romeike, Ralf; Schroeder, Ulrik; Schulte, Carsten (Frühe informatische Bildung - Ziele und Gelingensbedingungen für den Elementar- und Primarbereich. Berlin)

Kompetenzbasierte Gestaltungsempfehlungen für Informatik-Tutorenschulungen - Danielsiek, Holger; Hubwieser, Peter; Krugel, Johannes; Magenheim, Johannes; Ohrndorf, Laura; Ossenschmidt, Daniel; Schaper, Niclas; Vahrenhold, Jan (INFORMATIK 2017)

PERSPECTIVES FOR AN INTERDISCIPLINARY DATA SCIENCE CURRICULUM IN GERMAN SECONDARY SCHOOLS - Biehler, Rolf; Schulte, Carsten (Paderborn Symposium on Data Science Education at School Level)

Eye movements in code reading: relaxing the linear order - Busjahn, Teresa; Bednarik, Roman; Begel, Andrew; E. Crosby, Martha; H. Paterson, James; Schulte, Carsten; Sharif, Bonita; Tamm, Sascha (ICPC)

Proceedings of the 2015 ACM Conference on Innovation and Technology in Computer Science Education, ITiCS 2015, Vilnius, Lithuania, July 4-8, 2015

What influences dwell time during source code reading?: analysis of element type and frequency as factors - Busjahn, Teresa; Bednarik, Roman; Schulte, Carsten (ETRA)

Eye tracking in computing education - Busjahn, Teresa; Schulte, Carsten; Sharif, Bonita; Begel, Andrew; Hansen, Michael; Bednarik, Roman; Orlov, Paul; Ihantola, Petri; Shchekotova, Galina; Antropova, Maria (ICER)

Developing Coding Schemes for Program Comprehension using Eye Movements - Busjahn, Teresa; Schulte, Carsten; Kropp, Edna (PPIG)

Proceedings of the 9th Workshop in Primary and Secondary Computing Education, WiPSCE 2014, Berlin, Germany, November 5-7, 2014

The use of code reading in teaching programming - Busjahn, Teresa; Schulte, Carsten (Koli Calling)

Object Interaction Competence Model v. 2.0 - Bennedsen, Jens; Schulte, Carsten (LaTiCE)

PCK and reflection in computer science teacher education - Buchholz, Malte; Saeli, Mara; Schulte, Carsten (WiPSCE)

Reflections on the role of programming in primary and secondary computing education - Schulte, Carsten (WiPSCE)

Koli Calling 2009 and 2010 - Schulte, Carsten; Suhonen, Jarkko (Computer Science Education)

Computer science at school/CS teacher education: Koli working-group report on CS at school - Schulte, Carsten; Hornung, Malte; Sentance, Sue; Dagiene, Valentina; Jevsikova, Tatjana; Thota, Neena; Eckerdal, Anna; Peters, Anne-Kathrin (Koli Calling)

Uncovering structure behind function: the experiment as teaching method in computer science education - Schulte, Carsten (WiPSCE)

Analysis of code reading to gain more insight in program comprehension - Busjahn, Teresa; Schulte, Carsten; Busjahn, Andreas (Koli Calling)

ProspectiveTeachers@Research: CS teacher education revised - Hornung, Malte; Schulte, Carsten (Koli Calling)

Informatik begreifen - Zur Nutzung von Veranschaulichungen im Informatikunterricht - Kalbitz, Manuela; Voss, Hendrik; Schulte, Carsten (INFOS)

Das Schülerlabor als Ort der Informatiklehrerbildung - Schulte, Carsten (INFOS)

BlueJ Visual Debugger for Learning the Execution of Object-Oriented Programs? - Bennedsen, Jens; Schulte, Carsten (TOCE)

Comparison of OOP first and OOP later: first results regarding the role of comfort level - Ehlert, Albrecht; Schulte, Carsten (ITiCSE)

10th Koli Calling International Conference on Computing Education Research, Koli Calling '10, Koli, Finland, October 28-31, 2010

Didaktik der Informatik - Möglichkeiten empirischer Forschungsmethoden und Perspektiven der Fachdidaktik. 6. Workshop der GI-Fachgruppe "Didaktik der Informatik", 16. - 17. September 2010 in Oldenburg

An evaluation of object oriented example programs in introductory programming textbooks - Börstler, Jürgen; S. Hall, Mark; Nordström, Marie; H. Paterson, James; Sanders, Kate; Schulte, Carsten; Thomas, Lynda (SIGCSE Bulletin)

Qualitätssicherung in einer interaktiven und lerneraktivierenden E-Learning-Umgebung - Schulte, Carsten; Tolksdorf, Robert (DeLFI Workshops)

Empirical comparison of objects-first and objects-later - Ehlert, Albrecht; Schulte, Carsten (ICER)

Bridging ICT and CS: educational standards for computer science in lower secondary education - Brinda, Torsten; Puhlmann, Hermann; Schulte, Carsten (ITiCSE)

Unterschiede im Lernerfolg von Schülerinnen und Sch\üern in Abhängigkeit von der zeitlichen Reihenfolge der Themen (OOP-First bzw. OOP-Later) - Ehlert, Albrecht; Schulte, Carsten (INFOS)

Informatik im Kontext (IniK) - Ein integratives Unterrichtskonzept für den Informatikunterricht - Koubek, Jochen; Schulte, Carsten; Schulze, Peter; Witten, Helmut (INFOS)

Dualitätsrekonstruktion als Hilfsmittel zur Entwicklung und Planung von Informatikunterricht - Schulte, Carsten (INFOS)

Block Model: an educational model of program comprehension as a tool for a scholarly approach to teaching - Schulte, Carsten (ICER)

Duality Reconstruction - Teaching Digital Artifacts from a Socio-technical Perspective - Schulte, Carsten (ISSEP)

What are information technology's key qualifications? - Dörge, Christina; Schulte, Carsten (ITiCSE)

Digitale Artefakte und Schlüsselkompetenzen im Informatikunterricht der Sekundarstufe I - Schulte, Carsten; Dörge, Christina (DDI)

Attitudes towards computer science-computing experiences as a starting point and barrier to computer science - Schulte, Carsten; Knobelsdorf, Maria (ICER)

Lesen im Informatikunterricht - Schulte, Carsten (INFOS)

Das informatische Weltbild von Studierenden - Schulte, Carsten; Knobelsdorf, Maria (INFOS)

Social, ethical and technical issues in informatics - An integrated approach - Magenheim, Johannes; Schulte, Carsten (EAIT)

Research perspectives on the objects-early debate - Lister, Raymond; Berglund, Anders; Clear, Tony; Bergin, Joe; Garvin-Doxas, Kathy; Hanks, Brian; E. Hitchner, Lewis; Luxton-Reilly, Andrew; Sanders, Kate; Schulte, Carsten; L. Whalley, Jacqueline (SIGCSE Bulletin)

What do teachers teach in introductory programming? - Schulte, Carsten; Bennedsen, Jens (ICER)

A Competence Model for Object-Interaction in Introductory Programming - Bennedsen, Jens; Schulte, Carsten (PPIG)

Gestaltung von Informatikseminaren unter Einsatz von Videokonferenzen - Schulte, Carsten; Thomas, Marco (HDI)

3. Workshop der GI-Fachgruppe "Didaktik der Informatik", 19.-20. Juni 2006 an der Universität Potsdam

Novices' expectations and prior knowledge of software development: results of a study with high school students - Schulte, Carsten; Magenheim, Johannes (ICER)

Beiträge der Objektorientierung zu einem Kompetenzmodell des informatischen Modellierens - Brinda, Torsten; Schulte, Carsten (INFOS)

Erwartungen und Wahlverhalten von Schülerinnen und Schülern gegenüber dem Schulfach Informatik - Ergebnisse einer Umfrage - Schulte, Carsten; Magenheim, Johannes (INFOS)

Lehr-Lernprozesse im Informatik-Anfangsunterricht: theoriegeleitete Entwicklung und Evaluation eines Unterrichtskonzepts zur Objektorientierung in der Sekundarstufe II - Schulte, Carsten

Thinking in Objects and their Collaboration: Introducing Object-Oriented Technology - Schulte, Carsten; Magenheim, Johannes; Niere, Jörg; Schäfer, Wilhelm (Computer Science Education)

Theoriegeleitete Entwicklung und Evaluation von Neuen Medien für die Lehre - Schulte, Carsten (Softwaretechnik-Trends)

Theoriegeleitete Entwicklung und Evaluation von Neuen Medien für die Lehre - Schulte, Carsten (GI Jahrestagung)

Das Sieben-Schritte-Schema zur Dekonstruktion objektorientierter Software - Schulte, Carsten; Block, Ulrich (DDI)

Vom Modellieren zum Gestalten - Objektorientierung als Impuls für einen neuen Informatikunterricht? - Schulte, Carsten (Informatica Didactica)

Aufgabenbereiche der Medienbildung im Informatikunterricht - Schulte, Carsten; Scheel, Olaf (INFOS)

Kooperative Arbeitsplattformen - CSCW-Systeme in Lehr- und Lernkontexten - Schulte, Carsten; Selke, Harald; Huth, Carsten (LOG IN)

Dekonstruktion von Informatiksystemen als Unterrichtsmethode - Zugang zu objektorientierten Sichtweisen im Informatikunterricht - Hampel, Thorsten; Magenheim, Johannes; Schulte, Carsten (INFOS)